2017
DOI: 10.4132/jptm.2016.10.13
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of Hepatocellular Carcinoma after Liver Transplantation: Comparative Analysis with Partial Hepatectomy

Abstract: BackgroundLiver transplantation (LT) is the treatment of choice for hepatocellular carcinoma (HCC). The aim of this study was to investigate the recurrence rate of HCC after LT and prognostic factors for recurrence by comparing LT with non-transplanted resection. MethodsThe participants were 338 patients who underwent LT between 1996 and 2012 at Seoul National University Hospital (LT group) and 520 HCC patients who underwent partial hepatectomy between 1995 and 2006 (control group, non-LT group). ResultsIn the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In Lee's report (22), the overall recurrence rates for 388 patients with LT and 520 patients with LR were 0.198 and 0.649, respectively. Statistical level of α = 0.001 and β = 0.01 were used to compare the sample rates for each group, which required at least 62 patients for each group.…”
Section: Sample Size Calculationmentioning
confidence: 96%
“…In Lee's report (22), the overall recurrence rates for 388 patients with LT and 520 patients with LR were 0.198 and 0.649, respectively. Statistical level of α = 0.001 and β = 0.01 were used to compare the sample rates for each group, which required at least 62 patients for each group.…”
Section: Sample Size Calculationmentioning
confidence: 96%
“…Zheng et al [22] in 212 patients who underwent liver resection showed that 77% of the short term survivors developed recurrence within 2 years while 42% of the 10 year survivors developed recurrence most of whom had intrahepatic recurrences that were treatable. In a study of 878 patients with HCC, Lee et al [25] reported a 19.8% recurrence after transplant compared to a 64.9% recurrence after resection and suggested that transplant may have a protective effect against late recurrence of early stage HCC. Risk factors for recurrence included multiple tumors, tumor size, histologic features (grade, extent, vascular invasion) and preoperative AFP.…”
Section: Recurrencementioning
confidence: 99%